Pengaruh Status Gizi Terhadap Kejadian Stunting Pada Balita di Desa Pasie Lamgarot Kecamatan Ingin Jaya Kabupaten Aceh Besar - Kartika, Komala; Halizasia, Gadis (Teewan Journal Solutions, 2024)
The toddler years are included in the golden period for children's growth and development. Stunting can happen to anyone, this disease is caused by chronic lack of nutrition over a long period. The risk of stunting arises from the first 1,000 days of life. The high prevalence of stunting among toddlers in Indonesia requires efforts to address and prevent stunting from an early age. Handling stunting is carried out through specific interventions and sensitive interventions targeting the first 1000 days of a child's life up to the age of 6 years. To determine the effect of pregnant women's diet on the incidence of stunting among toddlers in Pasie Lamgarot Village, Ingin Jaya District, Aceh Besar Regency in 2024. This type of research is analytical observational research using a cross sectional approach. The population in this study were mothers and toddlers in Pasie Lamgarot Village. The sample for this study was purposive sampling, namely all mothers and toddlers in Pasie Lamgarot Village, Ingin Jaya District.Research Results: The nutritional status was good for 44 people (73.3%), and there were no stunting in toddlers, 16 people (26.7%) had poor nutritional status, 15 people (93.7%) experienced stunting and none 1 person (6.3%) experienced stunting. The results of the chi square statistical test obtained p=0.000 > 0.05, meaning that toodlers nutritional status influences the incidence of stunting among toddlers in Pasie Lamgarot Village.